2007
DOI: 10.1159/000099833
|View full text |Cite
|
Sign up to set email alerts
|

Does Periadventitial Fat-Derived Nitric Oxide Play a Role in Improved Saphenous Vein Graft Patency in Patients Undergoing Coronary Artery Bypass Surgery?

Abstract: Background/Aims: The saphenous vein is commonly used for coronary artery bypass surgery but its patency is poor. Vascular damage occurs during conventional surgery. However, patency improves when the graft is harvested with minimal surgical trauma, partly due to preservation of vascular endothelial nitric oxide synthase (eNOS) and tissue sources of nitric oxide (NO), a factor possessing both dilatory and anti-proliferative properties. Apart from these grafts exhibiting an intact luminal endothelium they are ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 59 publications
1
58
0
1
Order By: Relevance
“…Conduit harvesting is known to damage the endothelium and may reduce endothelial nitric oxide synthase and nitric oxide release 24,25 ; however, careful surgical technique may minimize endothelial damage of coronary conduits. 26,27 Shear stress is also known to affect graft endothelial function, and reducing shear stress during graft preparation may preserve endothelial integrity. 24,28 Details of the harvesting techniques used in the RSVP trial have been published previously.…”
Section: Discussionmentioning
confidence: 99%
“…Conduit harvesting is known to damage the endothelium and may reduce endothelial nitric oxide synthase and nitric oxide release 24,25 ; however, careful surgical technique may minimize endothelial damage of coronary conduits. 26,27 Shear stress is also known to affect graft endothelial function, and reducing shear stress during graft preparation may preserve endothelial integrity. 24,28 Details of the harvesting techniques used in the RSVP trial have been published previously.…”
Section: Discussionmentioning
confidence: 99%
“…30 In addition, Dashwood et al reported that perivascular fat-derived nitric oxide had a beneficial role in vein grafts that had been atraumatically harvested. 31 Finally, Souza et al 32 demonstrated that harvesting saphenous vein to be used in coronary bypass with its intact adventitia and surrounding tissues was associated with high short-and long-term patency rates of the venous grafts. Consequently, nowadays several authors propose the use of a "non-touch" technique during venous procurement to avoid (a) adventitial disruption that occurs when conventional harvesting techniques are used, and (b) the detrimental changes on the venous graft's function.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Second, echocardiography, computer tomography, magnetic resonance imaging (MRI) and other non-invasive imaging of heart-and artery-associated adipose tissue may identify the high-risk population susceptible to metabolic syndrome (30) and atherosclerosis (41,42) and monitor vascular wall changes during follow-up studies and therapeutic trials. Third, the "non-touch harvesting technique" is an example of appreciation of adipoparacrinology in coronary artery bypass surgery (43,44). Fourth, PAAT/tunica adiposa may represent a new therapeutic target (2, 3, 12, 24, 31-33), in artery bypass surgery also (45).…”
Section: Pericardiummentioning
confidence: 99%